PELATIHAN PEMBUATAN VCO DAN SIRUP DHT BAGI IBU-IBU PKK DESA PALLANTIKANG KECAMATAN PATTALASSANG KABUPATEN GOWA - Hastuti Hastuti; Andi Tenri Yeyeng; Hasria Alang (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
Utilization of natural resources around is one way to increase the economic value of these natural resources. Maximum utilization of natural resources can also improve the local community's economy. Providing education is one way to increase the knowledge and skills of the community. Due to the need for cooking oil and the desire to improve the standard of living of partners, the PKM team was conducted training with the theme of making VCO and DHT syrup for PKK mothers in Pallantikang Village, Gowa. This activity aims to improve the skills of housewives in Pallantikang Village through education on making DHT and VCO syrup as well as opportunities for businesses so as to increase family income. The method used in this activity is lecture and practice. This activity begins with giving a pretest to measure partners' knowledge. At the end of the activity, a posttest was carried out to measure the increase in partners' knowledge after being given training. The results of the dedication show that there has been an increase in the participants' knowledge. This is shown from the results of the pretest and posttest given. In addition, participants have gained new experience, so that later they can practice it to increase family income.